Experiential Marketing Creative Antecedence for Success of Brand Loyalty: The Users of Perfume for Body in Indonesia - Sugiyarti, Gita; Hendar, Hendar (International Review of Management and Marketing, 2017)
The main objective of this study is to develop a model of marketing conceptual on Creative Experiential Marketing in order to boost brand loyalty. The specific target of this study is to empirically test creative influence on experiential marketing. Purposive sampling technique is applied in the study the collect data. Samples are taken as many as 183 respondents of the users of perfume for body sold in Indonesia. Data in this study is collected by interview. Data collection is using the combination of open questions and closed questions which are given to respondents. Managerial finding in this study is developing creative experiential marketing to enhance brand loyalty. Keywords: Sense Marketing, Act Marketing, Creative Experiential Marketing, Brand Trust, Brand Loyalty. JEL Classifications: M5, M21